Acceptability and feasibility of using a blended quality improvement strategy among health workers to monitor women engagement in Option B+ program in Lilongwe Malawi - Wiza Kumwenda; Angela M. Bengtson; Shaphil Wallie; Tarsizious Chikaonda; Mitch Matoga; Agatha K. Bula; Jimmy Ba Villiera; Edith Kamanga; Mina C. Hosseinipour; Victor Mwapasa (BMC, 2024)
Abstract Option B + provides lifelong ART to pregnant and breastfeeding women with HIV to reduce mother-to-child transmission of HIV (eMTCT) and improve maternal health. The effectiveness of Option B + relies on continuous engagement, but suboptimal monitoring of HIV care hinders our measurements of engagement. Process mapping and quality improvement (PROMAQI) is a quality improvement strategy for healthcare workers (HCWs) to optimize complex processes such as monitoring HIV care. We assessed the acceptability and feasibility of the PROMAQI among HCWs and identified barriers and facilitators for PROMAQI implementation. A cross-sectional study using a mixed method approach was conducted from August 2021 to March 2022 across five urban health facilities participating in PROMAQI implementation n the Lilongwe district, Malawi. We assessed PROMAQI acceptability and feasibility at the end of the study. A 5-point Likert (1 = worst to 5 = best) scale tool was administered to 110 HCWs (n = 15-33 per facility) involved in PROMAQI implementationThese data were analysed using descriptive statistics Among the 110 HCWs, twenty-two (QI team (n = 11) and QI implementers (n = 11)) were purposively selected for in-depth interviews. Thematic analysis was conducted using deducted and inductive approaches. The theoretical framework for acceptability (TFA) was used to identify reasons for acceptability. The Consolidated Framework for Implementation Research (CFIR) was used to characterize the barriers and facilitators of PROMAQI implementation. HCWs recruited had a median age of 37 (32-43) years, 82.0% of whom were female. Most (42%) had completed secondary education, and 84% were nurses and community health workers. The median (IQR) acceptability and feasibility scores for the PROMAQI were 5 (IQR 4-5) and 4 (IQR 4-5), respectively. Reasons for high PROMAQI acceptability included addressing a relevant gap and improving performance. Perceived implementation barriers included poor work attitudes, time constraints, resource limitations, knowledge gaps, and workbook difficulties. The facilitators included communication, mentorship, training, and financial incentives. PROMAQI is a highly acceptable and feasible tool for monitoring engagement of women in Option B + . Addressing these barriers may optimize the implementation of PROMAQI. Scaling up PROMAQI may enhance retention in the Option B + program and facilitate eMTCT.